Ebersole & Hess' toward healthy aging: human needs & nursing response - Touhy, Theris A.; Jett, Kathleen Freudenberger; Ebersole, Priscilla; Hess, Patricia A., 1938- (St. Louis, Mo.: Elsevier/Mosby, 2012)
Grounded in the core competencies recommended by the AACN in collaboration with the Hartford Institute for Geriatric Nursing, The 8th edition of this textbook is a comprehensive resource on health promotion and maintenance for older adults and their caregivers. It includes coverage of communication, safety and ethical considerations, new genetic research, key aging issues, and common and uncommon conditions. Provides the knowledge needed to promote healthy lifestyle choices, properly address end-of-life issues, and provide effective, holistic care for older adults.
Foundations of Healthy Aging. Gerontological nursing and an aging society -- Health and wellness -- Theories of aging -- Physiological changes -- Culture, gender, and aging -- Communicating with older adults -- Foundations of Caring. Health assessment -- Laboratory values and diagnostics -- Geropharmacology -- The use of herbs and supplements -- Wellness and Function. Elimination, sleep, skin, and foot care -- Mobility -- Environmental safety and security -- Nutrition and hydration -- Wellness and Chronic Illness. Chronic conditions -- Care across the continuum -- Pain and comfort -- Mental health -- Cognitive impairment -- Healthy Aging for Elders and their Families. Economic, legal, and ethical issues -- Intimacy and sexuality Relationships, roles, and transitions -- Loss, death, and palliative care -- Self-actualization, spirituality, and transcendence.
Rev. ed. of: Toward healthy aging / Priscilla Ebersole ... [et al.]. 7th ed. c2008.
Includes bibliographical references and index.
Keywords: Geriatric nursing; Aging; Older people -- Health and hygiene; Geriatric Nursing; Aged; Aging; Health Promotion